'For me it's just the conversation:' responsive feeding influences among early childhood educators - Olga Levin; Jessie-Lee D McIsaac; Julie Campbell; Elizabeth Dickson; Melissa D Rossiter (Cambridge University Press, 2024)
Abstract Objective: Early learning and childcare (ELCC) programmes play an important role in shaping children's eating behaviours and long-term health by establishing a responsive feeding environment that encompasses not only mealtime behaviours but also extends to play activities and language used throughout the day. Despite their potential benefits, many ELCC centres do not consistently implement responsive feeding behaviours, facing challenges with organisational and behavioural changes within these environments. This study aims to identify influences on responsive feeding behaviours among early childhood educators prior to an intervention. Design: A qualitative study guided by the Behaviour Change Wheel framework and Capability Opportunity Motivation - Behaviour (COM-B) model. Semi-structured interviews and focus groups were conducted, recorded and transcribed verbatim. Thematic analysis was employed to identify themes, categorising them within the corresponding COM-B domains. Setting: Canada. Participants: Forty-one ELCC staff in various roles across eight centres from two provinces in eastern Canada. Results: Fifteen influences, spanning across all six domains of the COM-B model, were identified, highlighting gaps in educators' knowledge and skills, varied approaches to food and feeding, and the interactions with children, parents, and co-workers on mealtimes dynamics. Additionally, costs, centre location and other physical resources emerged as enabling opportunities for responsive feeding behaviours. Conclusions: These findings offer a comprehensive exploration of the diverse factors influencing responsive feeding behaviours among educators, each varying in its potential for future behaviour change intervention.